Analisis Orientasi Pasar dan Orientasi Kewirausahaan Terhadap Kinerja Pemasaran dan Inovasi UMKM Binaan KPw Bank Indonesia Provinsi Riau - Hanif; Zulkarnain; Eka Armis Pailis (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2022)
Indonesian MSMEs as the largest absorber of labor are expected to grow the export market. Riau Province is the area on the island of Sumatra that has the lowest market share index. This study aims to further test whether entrepreneurial orientation and market orientation have an effect on innovation and marketing performance. This research is explanatory research. The unit of analysis in this study is the MSME cluster fostered by Bank Indonesia in Riau Province in the Riau Province. The analysis used is Partial Least Square (PLS). The total population in this study was 277 MSMEs with a sample of 164 MSMEs from various clusters. Data collection techniques in this study used a questionnaire collected in the form of primary data. The results of this study indicate that market orientation has a significant effect on business innovation, entrepreneurial orientation has a significant effect on business innovation, market orientation has a significant effect on improving marketing performance, entrepreneurial orientation has a significant effect on marketing performance, business innovation has a significant effect on marketing performance, market orientation has a significant effect on marketing performance through business innovation, entrepreneurial orientation has a significant effect on marketing performance through business innovation.